(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2016)
Islamic law is the regulation implemented in Indonesia which is absorbed from product of law as stated in the various books of fiqh which has been written by the ulama such as about marriage, inheritance, zakat, wakaf and Hajj. To implement Islamic law in Indonesia, it needs presence for structure in the form of a legitimate institution. KUA is a government agency that has a role and duty to carry out the partially affairs of Islam religion in Indonesia.